On the linkages between stock prices and exchange rates: Evidence from the banking crisis of 2007-2010 - Guglielmo Maria Caporale; John Hunter; Faek Menla Ali (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This study examines the nature of the linkages between stock market prices and exchange rates in six advanced economies, namely the US, the UK, Canada, Japan, the euro area, and Switzerland, using data on the banking crisis between 2007 and 2010. Bivariate GARCH-BEKK models are estimated producing evidence of unidirectional spillovers from stock returns to exchange rate changes in the US and the UK, in the opposite direction in Canada, and of bidirectional spillovers in the euro area and Switzerland. Furthermore, causality-in-variance from stock returns to exchange rates changes is found in Japan and in the opposite direction in the euro area and Switzerland, whilst there is evidence of bidirectional feedback in the US and Canada. These findings imply limited opportunities for investors to diversify their assets during this period.
Keywords: F31; G15; C32; 330; Stock prices; Exchange rates; Causality-in-variance; Cointegration